Pengaruh Media Audio Visual Terhadap Sikap Toleransi Siswa Kelas V Sdn 064976: Penelitian - Suci Khairani Siregar; Sandy Despian Permana; Adhaniha Karimah Lubis; Amalia Nazlah Hutabarat; Hapni Laila Siregar (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
This study aims to examine how audiovisual media influence the tolerance attitudes of fifth-grade students at SDN 064976. The foundation of this research is the decline in students’ tolerance due to conventional teaching methods that are less engaging. The study employs a quantitative approach with a quasi-experimental design (one-group pretest-posttest). The participants consist of 30 students. Data were collected using a Likert scale survey that evaluated aspects of respecting differences, cooperation, and mutual appreciation. The findings show a significant improvement in students’ tolerance attitudes after the use of audiovisual media. The average pretest score of 44.083% increased to 89.208% in the posttest, indicating an improvement of 45.125%. These results demonstrate that audiovisual media can enhance students’ understanding and application of tolerance values by providing engaging, interactive, and easily comprehensible learning experiences. Therefore, the effective use of audiovisual media fosters tolerant character development among elementary school students.